Biodiesel Production from Microalgae by Extraction – Transesterification Method - Nguyen Thi Phuong Thao; Nguyen Thanh Tin; Bui Xuan Thanh (Diponegoro University, 2013)
The environmental impact of using petroleum fuels has led to a quest to find a suitable alternative fuel source. In this study, microalgae were explored as a highly potential feedstock to produce biodiesel fuel. Firstly, algal oil is extracted from algal biomass by using organic solvents (n–hexan). Lipid is contained in microalgae up to 60% of their weight. Then, Biodiesel is created through a chemical reaction known as transesterification between algal oil and alcohol (methanol) with strong acid (such as H2SO4) as the catalyst. The extraction – transesterification method resulted in a high biodiesel yield (10 % of algal biomass) and high FAMEs content (5.2 % of algal biomass). Biodiesel production from microalgae was studied through experimental investigation of transesterification conditions such as reaction time, methanol to oil ration and catalyst dosage which are deemed to have main impact on reaction conversion efficiency. All the parameters which were characterized for purified biodiesel such as free glycerin, total glycerin, flash point, sulfur content were analyzed according to ASTM standardDoi: http://dx.doi.org/10.12777/wastech.1.1.6-9Citation: Thao, N.T.P., Tin, N.T., and Thanh, B.X. 2013. Biodiesel Production from Microalgae by Extraction – Transesterification Method. Waste Technology 1(1):6-9. Doi: http://dx.doi.org/10.12777/wastech.1.1.6-9